Logements sociaux à Chongqing et à Shanghai. Corollaires de l’« urbanisation » rurale et de la financiarisation foncière - Miguel Elosua; Françoise Ged; YANG Chen (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Social housing in post-Maoist China reveals a complete paradigm shift, starting in the 1990s. Housing loses its status as a social benefit : allocated by companies (danwei) to their employees, it becomes a market, while the construction sector is a major stake for economic growth. A period during which multiple tenants' and owners' regimes coexisted developed until the housing reform, experimented in Shanghai at the beginning of the 1990s, then generalized throughout the country in 1998. The housing market dominated until the 12th Five Year Plan (2011-2015), which emphasized social housing.After presenting this context and the different categories of social housing, the article looks at Chongqing and Shanghai, where the issues are mutually illuminating. The government of the municipality of Chongqing has developed an intensive construction policy between 2007 and 2012, to attract rural people and "urbanize" them. To the north of Shanghai, the vast Gucun complex, built in 1998, brings together urban and rural dwellers with modest incomes, relocated after real estate or land transactions. Twenty years later, studies carried out by urban planners and sociologists from Tongji University are trying to identify and solve the problems of the large complex.The issues approached in different ways according to local governments show the interest of local studies to understand the complexity of a reform of national interest, with distinct temporalities and different regulatory approaches.